Whole-stream wastewater addition stimulates the green food web pathway but does not affect food chain length - Ioar de Guzman; Mario Brauns; Arturo Elosegi; Daniel von Schiller; Jose M. González; José M. Montoya; Aitor Larrañaga (Hydrobiologia, 2026)
Most rivers in developed regions receive tertiary-treated effluents from wastewater treatment plants that still contain a complex mixture of pollutants, but their combined effects on food webs are poorly understood. We had the unique opportunity to divert treated effluent into a previously pristine stream and conduct a before-after/control-impact/paired experiment to quantify effluent effects on green and brown food web pathways (i.e., algae and detritus-based pathways) and total food chain length. We hypothesized that the increased biofilm biomass after the effluent addition would promote its consumption by primary consumers, thus favoring the green pathway. Moreover, we hypothesized that the increase in the primary production would lead to an increase in food chain length. Coarse detritus remained the main food resource for primary consumers, but the addition of the effluent promoted biofilm biomass and increased the relative importance of the green food web pathway. However, the effluent discharge did not impact food chain length. The present study reveals that properly treated and substantially diluted effluents can still affect food web pathways through changes in dietary composition of consumers. Thus, further reducing nutrient inputs from WWTPs would minimize the impacts of effluents on food webs.